Total phenolics, tannin contents, antioxidant properties, protein and sensory analysis of Pleurotus ostreatus, Pleurotus citrinopileatus and Pleurotus djamor cultivated on different sawdusts - Kılıç, Ceyhun; Gürgen, Ayşenur; Yıldız, Sibel; Can, Zehra; Değirmenci, Atiye (Maderas. Ciencia y Tecnología, 2024)
In mushroom cultivation, it is important to be aware of the impact of the growing substrate. This study investigated the cultivation of various oyster mushrooms, including Pleurotus ostreatus, Pleurotus citrinopileatus, and Pleurotus djamor, on different types of wood sawdust. Total phenolic content, condensed tannins, antioxidant activity by ferric reducing antioxidant power assay, protein and sensory evaluations were performed in cultivated oyster mushrooms. Wood sawdust of Fagus orientalis (oriental beech), Alnus glutinosa (alder), Castanea sativa (chestnut), and Juglans regia (walnut) were used as substrate for studied mushroom type, separately. Because champignon (Agaricus bisporus) was the most consumed mushroom, it was used as control sample. Methanolic extracts of dried mushrooms were used to measure bioactive characteristics. Pleurotus ostreatus samples cultivated in Alnus glutinosa (alder) sawdust substrate had the highest antioxidant activity. The lowest antioxidant activity values were found in Pleurotus djamor cultivated in Juglans regia (walnut) wood sawdust substrate. The highest protein content was measured in Agaricus bisporus as 13,84 %. The other highest protein concentration was found in Pleurotus ostreatus cultivated in Alnus glutinosa (alder) sawdust substrate, at 13,75 %. The lowest protein concentration belonged to Pleurotus citrinopileatus cultivated in Fagus orientalis (oriental beech) sawdust substrate as 9,86 %. While Agaricus bisporus and Pleurotus ostreatus had the highest overall appreciation score, Pleurotus citrinopileatus had the lowest. It has been observed that the substrate content has an important impact on chemical and sensory properties of the oyster mushrooms. This study provides knowledge on the chemical and sensory characteristics of three different Pleurotus mushroom species cultivated on different composts.